(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2017)
The aim of this essay is to discuss, from a critical legal perspective, the limits of welfare - understood as the set of social protection policies that have come to be called, in European history, the welfare state - in the context of peripheral capitalist economies, with a special focus on the Brazilian case. In other words, the problem under analysis consists of investigating how the dogma of social rights and its difficulties can encourage or limit the construction of a welfare state, in order to provide data for the analysis of the possibility of law contributing to human emancipation, and in what terms. This essay cannot be understood in all its implications on its own. It is closely linked to the author’s recent academic output, to which the reader will be referred when relevant, thus avoiding the repetition of approaches that have already been developed in greater detail and depth elsewhere. Despite this, it will not be possible to avoid summarizing some of the theoretical propositions formulated previously, so that the text will constantly seek to avoid, in addition to repetitiveness, the risk of becoming lacunose. The idea is to articulate an interpretation of social rights in relation to the state without losing sight of the dogmatic categories that organize this phenomenon at the legal level, so that the work succeeds in its objective of effectively formulating an immanent critique of law. Given these objectives and the method proposed for its approach, the essay will initially investigate in what terms social rights are placed before legal dogma. From there, it will be necessary to investigate the relationship between social protection and the state in contemporary times, to then focus on the organization of state funding at various moments in its history throughout the 20th century and, finally, the implications of this for the legal dogma of social rights, hoping to achieve the objectives proposed in conclusion.